Vacancies in SnSe single crystals in a near-equilibrium state - Šraitrová, Kateřina; Čížek, Jakub; Holý, Václav; Plecháček, Tomáš; Beneš, Ludvík; Jarošová, Markéta; Kucek, Vladimír; Drašar, Čestmír (American Physical Society, 2019)
The development of intrinsic vacancies in SnSe single crystals was investigated as a function of annealing temperature by means of positron annihilation spectroscopy accompanied by transport measurements. It has been demonstrated that two types of vacancies are present in single-crystalline SnSe. While Sn vacancies dominate in the low-temperature region, Se vacancies and vacancy clusters govern the high-temperature region. These findings are supported by theoretical calculations enabling direct detection and quantification of the most favorable type of vacancies. The experiments show that Sn vacancies couple with one or more Se vacancies with increasing temperature to form vacancy clusters. Interestingly, the clusters survive the α→β transition at ≈800 K and even grow in size with temperature. The concentration of both Se vacancies and vacancy clusters increases with temperature, similar to thermoelectric performance. This indicates that the extraordinary thermoelectric properties of SnSe are related to point defects. We suggest that either these defects vary the band structure in favor of high thermoelectric performance or introduce an energy-dependent scattering of free carriers realizing, in fact, energy filtering of the free carriers. Cluster defects account for the glasslike thermal conductivity of SnSe at elevated temperatures.
Vakance v monokrystalech SnSe ve stavu blízkém rovnováze
Keywords: thermoelectricity; termoelektřina; SnSe; single crystals; vacancies; SnSe; monokrystaly; vakance